Bidentate Disilicate Framework for Bis‐Grafted Surface Species. Issue 47 (29th July 2021) - Ishizaka, Yusuke; Arai, Natsumi; Matsumoto, Kazuhiro; Nagashima, Hiroki; Takeuchi, Katsuhiko; Fukaya, Norihisa; Yasuda, Hiroyuki; Sato, Kazuhiko; Choi, Jun‐Chul
Abstract: Recent advances in surface organometallic chemistry have enabled the detailed characterization of the surface species in single‐site heterogeneous catalysts. However, the selective formation of bis‐grafted surface species remains challenging because of the heterogeneity of the supporting surface. Herein, we introduce a metal complex bearing bidentate disilicate ligands, −OSi(O t Bu)2 OSi(O t Bu)2 O−, as a molecular precursor, which has a silicate framework adjacent to the metal (Pt) center. The grafting of the precursors on silica supports (MCM‐41 and CARiACT Q10) proceeded through a substitution reaction on the silicon atoms of the disilicate ligand, which was verified by the detection of isobutene and t BuOH as the elimination products, to selectively yield bis‐grafted surface species. The chemical structure of the surface species was characterized by solid‐state NMR, and the chemical shift values of the ancillary ligands and 195 Pt nuclei suggested that the bidentate coordination sphere was maintained following grafting. Abstract : A molecular precursor bearing a bidentate disilicate ligand, −OSi(O t Bu)2 OSi(O t Bu)2 O−, was grafted on silica supports by substitution reaction on silicon atoms of the disilicate ligand to selectively form bis‐grafted surface species.